Adam-9 expression in squamous cell carcinoma, adenocarcinoma and adenosquamous cell carcinoma of the uterine cervix - Mohd Isa, Seoparjoo Azmel (2012)
Introduction: Cervical cancer is a preventable and the third most common cancer to occur in the reproductive age women. It is caused by the Human Papilloma Viruses. The ADAM 9 protein is involved in basement membrane degradation and tumor metastasis in certain types of tumor. Objective: Objectives of this study are to describe the characteristics of cervical cancer and factors associated with ADAM 9 expression in cervical cancer. Methodology: Retrospective record review was done in February 2012 using patients’ case notes obtained from the Medical Record Unit, Universiti Sains Malaysia Hospital. Data was entered and analyze using SPSS version 19. Result: There were 95 cases of cervical cancer included in this study. Majority were Malays 76 (80.0%), non smoker 85 (89.5%), without co-morbid disease (86.4%), had no distant metastasis 54 (56.8%) and absent of lymph nodes involvement 71 (74.7%). Squamous cell carcinoma was the most common type of cervical cancer 67 (70.5%). Mean age of subjects were 53.89 (10.83). The statistically significant associated factors for ADAM9 positive staining among cervical cancer were tumor size (p=0.004), distant metastasis (p=0.009) and histological type of cervical cancer, which is squamous cell carcinoma (p=0.017). Women with squamous cell carcinoma of cervical cancer has 7.39 times odds of having ADAM9 staining positive as compared with women with adenocarcinoma of cervical cancer (95% CI 1.42, 38.51; p=0.017). Cervical cancer patients who had distant metastasis has 12.82 times chances of having ADAM9 staining positive as compared with cervical cancer patients without distant metastasis (95% CI 1.91, 86.13; p=0.009). while with every 1mm increment in tumor size, women with cervical cancer will had 1.08 odds times od having ADAM9 staining positive (95% CI 1.02, 1.13; p=0.004). Conclusion: In this study we identified that ADAM 9 expression associated with large size of the tumor, lymph nodes involvement, distant metastasis and also type of carcinoma. This concludes that aggressive tumor expressed ADAM 9